Cyclic behavior and design methodology of exposed base plates with extended anchor bolts. (1st June 2022) - Torres-Rodas, Pablo; Medalla, Miguel; Zareian, Farzin; Lopez-Garcia, Diego
Highlights: Analytical study on a type of column base connection: Exposed Base Plate with Extended Anchor Bolts. Excellent behavior in recent major earthquakes (e.g., 2010 Chile earthquake) Plastic deformations occur only at the anchor bolts, and all other components of the connection (including the column) remain elastic. Flag-shape, self-centering hysteretic behavior. A rational design methodology is proposed and validated. Abstract: This paper investigates the behavior of a ductile detail of exposed base plates. This detail consists of a base plate anchored to the concrete foundation through bolts extended to a steel chair configuration. The intention is to concentrate plastic strains mainly in the extended region of the anchor bolts, forcing the other connection components to remain elastic. The scientific background of this research consists of a series of sophisticated nonlinear finite element models subjected to a cyclic load protocol in the presence of an axial compressive force. The models were validated against an experimental test reported in the literature. Forces within the connection components, stresses, strain distributions, and deformation modes were examined. A total of sixteen three-dimensional nonlinear models were created using the ABAQUS simulation platform. The models were separated into two groups: the first consists of models with dimensions similar to the specimens tested in recent experimental programs reported in the past, while the second group simulates connections representative of mid-rise industrial frames. Building on the insights gained from the simulations of the first group, a methodology is proposed to design these column base connections. This suggested methodology is validated with the second group of simulations. Results indicate that the studied configuration detail presents some advantages compared with the traditional detail presented in Design Guide 1. For instance, plastic strains are developed almost exclusively in the anchor rods, and no damage is expected at the remaining components. Another essential characteristic is the exposed stretch length, with which it is possible to achieve a target design rotation without significant strain concentrations in the anchor rods. This characteristic facilitates post-earthquake inspections and repairs, and damage is virtually eliminated in the first story.